ISYKALIYAH TARJAMAH AL-NUSHUS AL-ADABIYAH AL-INJLIZIYAH ILA AL-LUGHAH AL-'ARABIYAH - Abdul Khodir, Shafiyah Binti (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2016)
This study aims to shed light on the application of translation in translating literary texts. It also attempts to discuss this specialized art based on the problems of translating literary texts faced by the students especially from English to Arabic. The researcher adopted the descriptive and analytical methodologies where she has given a full account of Arabic and English culture backgrounds as well as literary genres of these two languages. In addition, the researcher analyzes a number of 21 students’ perceptions about William Shakespeare’s “A Midsummer’s Night Dream” which translated from English into Arabic and their difficulties in understanding the meaning of the text. The results of the study have shown that most of the respondents enjoyed reading translated literary texts from English to Arabic even though they encountered some difficulties to understand the meaning. They also believe that reading translated literary texts will enhance their language competency and vocabulary.DOI : 10.15408/a.v3i1.3188